PENGARUH IKLAN MEDIA TELEVISI DAN HARGA SERTA KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DAN KEPUASAN PELANGGAN LAYANAN INTERNET AXIS DI AXIS SHOP KOTA MALANG - I Gede Putu Widia Dharma; Mohammad Dimyati,; Sudaryanto Sudaryanto (RELASI : JURNAL EKONOMI, 2014)
The purpose of this study was to analyze the effect of advertising on television price and quality of products on purchasing decisions and customer satisfaction axis internet service at Axis shop Malang. Data was collecting by distributing questionnaires to 105 respondents who have selected by simple random sampling technique. To analyze the data, used Strusctural equation modeling (SEM). The analysis showed that the total effect of television advertising media significantly positive influence on purchase decisions of 0.383 with P causality test results of 0.002 (P <0.05), prices significantly positive influence on purchase decisions of 0.239 with P causality test results of 0.047 (P <0.05), quality of products significant positive effect on purchase decisions of 0.234 with P causality test results of 0.036 (P<0.05), adv. television media significant positive effect on satisfaction of 0.370 with P causality test results of 0.024 (P <0.05), the price of significant positive effect on satisfaction was 0.362 with P causality test results of 0.013 (P <0.05), affect product quality positively to the satisfaction of 0.239 with P causality test results of 0.088 (P>0.05), a significant positive influence purchasing decisions on satisfaction of 0.298 with P causality test results of 0.029 (P <0.05)